Comparison of patients in three different rehabilitation settings after knee or hip arthroplasty: a natural observational, prospective study. Issue 1 (December 2015) - Benz, T.; Angst, F.; Oesch, P.; Hilfiker, R.; Lehmann, S.; Mueller Mebes, C.; Kramer, E.; Verra, ML
Abstract Background Patients after primary hip or knee replacement surgery can benefit from postoperative treatment in terms of improvement of independence in ambulation, transfers, range of motion and muscle strength. After discharge from hospital, patients are referred to different treatment destination and modalities: intensive inpatient rehabilitation (IR), cure (medically prescribed stay at a convalescence center), or ambulatory treatment (AT) at home. The purpose of this study was to 1) measure functional health (primary outcome) and function relevant factors in patients with hip or knee arthroplasty and to compare them in relation to three postoperative management strategies: AT, Cure and IR and 2) compare the post-operative changes in patient's health status (between preoperative and the 6 month follow-up) for three rehabilitation settings. Methods Natural observational, prospective two-center study with follow-up. Sociodemographic data and functional mobility tests, Timed Up and Go (TUG) and Iowa Level of Assistance Scale (ILOAS) of 201 patients were analysed before arthroplasty and at the end of acute hospital stay (mean duration of stay: 9.7 days +/− 3.9). Changes in health state were measured with the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) before and 6 months after arthroplasty. Results Compared to patients referred for IR and Cure, patients referred for AT were significantly younger and less comorbid. Patients admitted to IR had the highest functional disability before arthroplasty. Before rehabilitation, mean TUG was 40.0 s in the IR group, 33.9 s in the Cure group, and 27.5 s in the AT group, and corresponding mean ILOAS was 16.0, 13.0 and 12.2 (50.0 = worst). At the 6 months follow-up, the corresponding effect sizes of the WOMAC global score were 1.32, 1.87, and 1.51 (>0 means improvement). Conclusions Age, comorbidity and functional disability are associated with referral for intensive inpatient rehabilitation after hip or knee arthroplasty and partly affect health changes after rehabilitation.